Wizerunek Górnego Śląska i Ślązaków w kategoriach rozwoju gospodarczego i pracowitości a postawy polityczne Polaków - Wojtkowski, Łukasz (Political Preferences, 2013)
The fie1d of ana1ysis presented in the artic1e are the findings of an ana1ysis of cognitive image of Si1esia and Si1esian in context of two categories. First is the economic deve1opment of the region, and second one is the di1igence of Si1esians. Answers given by respondents was depicted in prism of their po1itica1 attitudes and ideo1ogica1 be1iefs. It a11owed to point out specific patterns signi- fying about strong image position of Si1esia and its inhabitants autonomous1y of po1itica1 and ideo1ogica1 approaches of communication recipients.